The influences of substrates' physical properties on enzymatic PET hydrolysis: Implications for PET hydrolase engineering. Issue 1 (24th March 2022) - Pasula, Rupali Reddy; Lim, Sierin; Ghadessy, Farid J.; Sana, Barindra
Abstract: Plastic pollution in diverse terrestrial and marine environments is a widely recognised and growing problem. Bio‐recycling and upcycling of plastic waste is a potential solution to plastic pollution, as these processes convert plastic waste into useful materials. Polyethylene terephthalate (PET) is the most abundant plastic waste, and this material can be degraded by a class of recently discovered bacterial esterase enzymes known as PET hydrolases (PETase). Investigations of the enzymatic hydrolysis of diverse PET molecules have clearly revealed that the biodegradability of various PET substrates depends on both their chemical structure and physical properties, including polymer length, crystallinity, glass transition temperature, surface area, and surface charge. This review summarises the known impacts of crystallinity and other physical properties on enzymatic PET hydrolysis.